Will bryophytes survive in a warming world? - He, Xiaolan; He, Kate S.; Hyvönen, Jaakko (Perspectives in plant ecology, evolution and systematics, 2016)
•Bryophytes possess relatively low temperature optima for photosynthesis.•The range of temperatures for net photosynthetic gain of bryophytes is rather narrow.•Bryophytes are highly sensitive to elevated temperatures in hydrate state.•Bryophytes are under significant physiological pressure due to recent climate change.•The decline of bryophyte diversity will lead to alternations of ecosystems. Understanding how plant species respond to climate change is one of the great challenges in biodiversity conservation and sustainable ecosystem planning. Current studies of the impact of climate change on plants are biased to tracheophytes, i.e. vascular-plants. Only a few studies have been carried out on bryophytes despite the fact that they are ecologically equally important groups of embryophytes with their origins predating contemporary vascular-plants. Bryophytes fundamentally differ from vascular-plants in their small size and utilization of a poikilohydric strategy for water and nutrients; their survival and reproduction are highly dependent on their external environment. Thus, the results from studies of tracheophytes cannot be generalized on bryophytes. In this review, we synthesize information about the influence of environmental factors on bryophytes to understand their relation to climate, especially to temperature on a global scale. We discuss a range of critical topics, including the responses of photosynthetic activities to temperature changes, and the consequences of temperature change on the interactions between bryophytes and vascular-plants, as well as on peatland ecosystems. As many species thrive in relatively low temperatures, with a low potential for short-term thermal acclimation to higher temperature in a hydrated state, elevated temperatures may shorten the time of metabolic activity, and increase desiccation intensity. This can bring significant physiological pressure on the survival of poikilohydric bryophytes. As a consequence of global warming, significant losses in bryophyte diversity can be expected, particularly in areas harbouring large number of species such as boreal forests of higher latitudes, alpine biomes and higher altitudes on tropical mountains. Furthermore, the decline of bryophyte diversity will ultimately lead to an alteration of ecosystem structure and function, nutrient cycling, and carbon balance. Further exploration of bryophyte ecophysiology in the changing environment, particularly the acclimation potential of photosynthesis and its biochemical and enzyme level basis to predicted changes in temperature will provide new knowledge that will assist bryophyte conservation.